The Future of World Triathlon. From global connector to commercial catalyst (Deloitte, World Triathlon, 2025)
On July, 25th, World Triathlon unveiled the much-anticipated "Future of World Triathlon" report—developed in partnership with Deloitte—which lays out a potential strategic vision to unlock triathlon`s untapped commercial and global opportunities. World Triathlon President Antonio Fernández Arimany emphasised the importance of the findings of the Study: "This is more than a report—it is a guide for transformation. Triathlon must evolve to thrive. We will embrace the future with purpose, clarity, and renewed ambition to make our sport stronger, more visible, and more inclusive."